Factors affecting self-perceived readiness for community pharmacy advanced pharmacy practice experience (APPE) among undergraduate pharmacy students in University of the Philippines College of Pharmacy (UPCP) - Ambut, Gieberline Dyne A.; Domez, Kyla Mari F.; Gloria, Mac Ardy J. (Manila College of Pharmacy, University of the Philippines Manila, 2025)
The COVID-19 pandemic has prompted a shift from traditional face-to-face to online learning within Philippine pharmacy schools, requiring modifications in the BS Pharmacy curriculum to address immediate challenges posed. While existing literature has explored the impact of the pandemic on pharmacy education, gaps remain in understanding how online learning affects Advanced Pharmacy Practice Experience (APPE) readiness. This study aimed to explore the factors affecting self-perceived readiness of pharmacy undergraduates from the University of the Philippines College of Pharmacy (UPCP) towards APPE in the community setting following the transition to online learning. We utilized a quantitative, descriptive, cross-sectional research design and administered a 45-item survey to 55 students selected via stratified random sampling, which included 32 fourth-year and 23 fifth-year BS Pharmacy students. The questionnaire was tested for internal reliability (Cronbach’s alpha coefficient), while accuracy and relevance was checked via face and content validity. Data was analyzed using descriptive statistics and multinomial logistic regression (p<0.05) via MS Excel and Stata (ver 12). Participants had an average age of 22.64 (±0.95) years, majority of which were females (56%), and from Luzon (47%). All used at least one device, which the majority personally owned (98.18%) with stable performance (72.73%), which were mainly laptops (94.54%), and relied on mobile data (72.73%). More students had access to stable internet connection (52.73%) but there was still a considerable amount with intermittent connectivity (47.27%). Students strongly agreed that lack of motivation and the difficulty to concentrate during online classes was a barrier to online learning. Participants mostly agreed that fundamental APPE subjects adequately prepared them with the necessary knowledge and skills for community pharmacy APPE with the exception of Pharm 125 and 125, Pharm 116, and Pharm 136 as they reported a neutral stance. Both year levels agreed that they possess the necessary knowledge and skills for community pharmacy APPE. Lastly, sociodemographic characteristics did not influence readiness; however, the number of devices used (p=0.047) influenced knowledge-based readiness outcomes while Clin Pharm 160: Pharmacy Operations (p=0.016), Pharm 136: Legal Pharmacy (p=0.019), challenging online learning materials (p=0.008), lack of motivation (p = 0.036), physical health (p = 0.037), and mental health (p = 0.024) influenced skills-based readiness outcomes. Undergraduate pharmacy students perceived themselves as ready for community pharmacy APPE in terms of both knowledge and skills. Their self-perceived readiness was significantly associated with access to technology, availability of technology, and self-perceived barriers encountered during online learning. Findings from this study provided evidence for curriculum revision in terms of identifying areas for improvement and in developing strategies to maximize APPE readiness.
Thesis (Bachelor of Science in Pharmacy)--University of the Philippines Manila, June 2025
Keywords: Pharmaceutical education -- Experiential learning -- Community pharmacy -- Philippines; Pharmacy students -- Self-perceived readiness -- Advanced pharmacy practice experience -- Philippines .; Professional competence -- Undergraduate pharmacy students -- Community pharmacy practice -- Philippines; APPE; advanced pharmacy practice experience; online learning; pharmacy education; readiness, factors